Effect of Foreign Flow, Stock Transaction Volume and Bid-Ask Spread on Stock Prices: Pengaruh Foreign Flow, Volume Transaksi Saham dan Bid-Ask Spread Terhadap Harga Saham - Nurcahyani, Amaliasari; Sari, Herlinda Maya Kumala (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of foreign flow, stock transaction volume and bid-ask spread on stock prices. This research is a type of quantitative research and population collection and the sample of the research object is carried out using the purposive sampling method, namely pharmaceutical companies listed on the IDX during the 2018-2020 period. The type of data used in this study is secondary data taken from the annual reports of each company sourced from the Indonesia Stock Exchange website. The data analysis technique used panel data regression using Eviews 10. The results showed partially that the Foreign Flow variable did not have a significant effect on the Stock Price, the Stock Transaction Volume had a significant positive effect on the Stock Price and the Bid-Ask Spread had a significant negative effect on the Stock Price. . Meanwhile, simultaneously all independent variables have a significant effect on stock prices.